2002
DOI: 10.1038/sj.bmt.1703413
|View full text |Cite
|
Sign up to set email alerts
|

Changing pattern of bacterial susceptibility to antibiotics in hematopoietic stem cell transplant recipients

Abstract: Summary:Adequate infection prophylaxis and empirical antibiotic therapy are of critical importance after hematopoietic stem cell transplantation (HSCT). We examined the evolution of bacterial susceptibility to antibiotics in 492 patients (198 allografts and 294 autografts) transplanted between 1982 and 1999 and evaluated whether ciprofloxacin prophylaxis and an empirical antibiotic regimen (glycopeptide + third-generation cephalosporin) were still valid. We collected all susceptibility tests performed during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
2
14
0
1
Order By: Relevance
“…22,23 Rates of VRE colonization are increasingly reported in those who undergo HSCT, ranging from 10% to as high as 40% at some centers 24,25 ; however, numerous epidemiologic studies have noted a marginal (<5%) incidence of VRE infection in the HSCT patient population. 12,15,19 Although the earlier time period of our study is consistent with these trends, a few concerning features were identified. First, 5 VRE infections occurred in 2007, which could represent either a contained outbreak or a more generalized trend of increased VRE prevalence in our allogeneic HSCT patient population.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…22,23 Rates of VRE colonization are increasingly reported in those who undergo HSCT, ranging from 10% to as high as 40% at some centers 24,25 ; however, numerous epidemiologic studies have noted a marginal (<5%) incidence of VRE infection in the HSCT patient population. 12,15,19 Although the earlier time period of our study is consistent with these trends, a few concerning features were identified. First, 5 VRE infections occurred in 2007, which could represent either a contained outbreak or a more generalized trend of increased VRE prevalence in our allogeneic HSCT patient population.…”
Section: Discussionsupporting
confidence: 66%
“…[16][17][18][19] Fluoroquinolone-resistant and MDR P aeruginosa and E coli were frequently identified in our allogeneic HSCT patients who received fluoroquinolonebased combination antimicrobial prophylaxis. These findings are consistent with a recent study describing prophylactic fluoroquinolone use as a risk factor for the isolation of MDR E coli in a broad neutropenic population.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Recently, the widespread emergence of FQ-resistant or multidrug-resistant microorganisms in hematologyoncology units has been suggested to compromise the effectiveness of routine antibacterial prophylaxis with FQs in patients undergoing cytotoxic chemotherapy or HCT. [6][7][8][9][10][11][12][13][14] In our center, the isolation rate of FQ-resistant Gramnegative bacilli was high (57.1%) during a period when FQs were routinely administered as antibacterial prophylactic agents; in particular, among isolated Enterobacteriaceae strains, 66.7, 33.3 and 22.2% were resistant to levofloxacin, piperacillin and ceftazidime, respectively. 8 In an attempt to reduce the emergence of antibiotic-resistant microorganisms, we stopped using any antibacterial prophylaxis in both autologous and allogeneic HCT recipients in 2004, 8 and found that this discontinuation of FQ prophylaxis, even in the setting of myeloablative allogeneic HCT did not significantly affect early mortality after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…1 There has been a concomitant trend toward antimicrobial resistance in both Gram-positive and Gram-negative bacteria. [1][2][3] The development of vancomycin resistance in enterococci has been a difficult challenge for both the clinician and the infection control practitioner. 4 In one outbreak involving leukemic patients, the mortality rate was 73%.…”
mentioning
confidence: 99%